The Promise of Lean Experimentation - and Murray, Peter; Ma, Steve (Stanford Social Innovation Review, 2015)
By adopting a model from business, nonprofit organizations can launch, test, and implement new programs and services more efficiently. Includes magazine extras.
Keywords: IMPORTANT